2021
DOI: 10.3390/brainsci11050655
|View full text |Cite
|
Sign up to set email alerts
|

Is the Age of Developmental Milestones a Predictor for Future Development in Down Syndrome?

Abstract: Down Syndrome (DS) is the most common genetic alteration responsible for intellectual disability, which refers to deficits in both intellectual and adaptive functioning. According to this, individuals with Down Syndrome (DS) reach developmental milestones (e.g., sitting, walking, and babbling) in the same order as their typically developing peers, but later in life. Since developmental milestones are the first blocks on which development builds, the aims of the current study are to: (i) expand the knowledge of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 61 publications
5
12
0
Order By: Relevance
“…Regarding cognitive function, our results indicated that TS mice showed cognitive delay during early stages of development. As suggested in clinical investigations (Locatelli et al, 2021;J. Luis Olmos-Serrano et al, 2016), the cognitive alterations continued with development, and adult TS mice showed hyperactivity, impaired memory robustness, and more explorative behavior, in line with previous reports (Aziz et al, 2018;Costa et al, 2010;Coussons-Read & Crnic, 1996;Dierssen et al, 2002;Escorihuela et al, 1995;Escorihuela et al, 1998;Holtzman et al, 1996;Llambrich, González, et al, 2022;J.…”
Section: Functional Domainsupporting
confidence: 77%
“…Regarding cognitive function, our results indicated that TS mice showed cognitive delay during early stages of development. As suggested in clinical investigations (Locatelli et al, 2021;J. Luis Olmos-Serrano et al, 2016), the cognitive alterations continued with development, and adult TS mice showed hyperactivity, impaired memory robustness, and more explorative behavior, in line with previous reports (Aziz et al, 2018;Costa et al, 2010;Coussons-Read & Crnic, 1996;Dierssen et al, 2002;Escorihuela et al, 1995;Escorihuela et al, 1998;Holtzman et al, 1996;Llambrich, González, et al, 2022;J.…”
Section: Functional Domainsupporting
confidence: 77%
“…Generally, it was assumed that infants and children with DS reached developmental milestones in the same linear fashion as their non-DS peers, but at later chronological ages. This view is too simplistic, as the age of acquiring milestones among infants and children with DS is reported to vary significantly ( 21 , 22 ). For example, the mean age at the onset of babbling is ~15 months, with an interindividual variability of 10 months.…”
Section: Infants Children and Adolescents With Ds: Variability In Developmental Outcomesmentioning
confidence: 99%
“…For example, the mean age at the onset of babbling is ~15 months, with an interindividual variability of 10 months. Similarly, sphincter control is acquired by DS children at an approximate age of 44 months, with 22 months of interindividual variability ( 22 ). Notably, Locatelli et al suggested that the age at which developmental milestones are reached influences the subsequent development of diverse cognitive domains significantly ( 21 , 22 ).…”
Section: Infants Children and Adolescents With Ds: Variability In Developmental Outcomesmentioning
confidence: 99%
“…Indeed, previous studies found that gestures predict language development in children with typical development and DS ( Capone and McGregor, 2004 ; Rowe et al, 2008 ; Zampini and D’Odorico, 2009 ). In addition, (i) the use of gestures at 24 and 36 months of age has been shown to predict future vocabulary growth ( Zampini and D’Odorico, 2009 ), (ii) early prosodic development predicted lexical development in similar ways for infants and toddlers with typical development, at-risk for language impairments, or with DS ( Sousa et al, 2022 ), (iii) babbling correlated with later language development ( Locatelli et al, 2021 ) in line with previous studies on TD children (e.g., Lang et al, 2019 ), and (iv) the relationship between motor and language development was found to become stronger as the age of children increases ( Yamauchi et al, 2019 ), a pattern that is also consistent with findings for TD children (e.g., Alcock and Krawczyk, 2010 ).…”
Section: Introductionmentioning
confidence: 99%